Indução da tolerância a estresses abióticos na germinação de sementes de arroz de terras altas com uso de moléculas sinalizadoras - Ribeiro, Jéssica Batista (2022)
Rice is an important food in the diet of the world population, as it is an excellent source of energy, vitamins and essential proteins for man. Despite the importance of production not keeping up with demand, it is necessary to develop new tolerant cultivars for planting under conditions of deficit and high temperatures. Upland rice is vulnerable to drought and high temperature stresses. Under these reduction reduction in plant height, decrease in profile reduction number, reduction number conditions, reduction of biomass accumulation and grain yield, flowering delay, spikelet sterility, reduction of grain reduction number and by reduced productivity. In addition, there is an increase in the production of reactive oxygen species (ROS), which can lead to the emergence of oxidative springs, giving rise to oxidative activity. ROS, cells, cells, enzymatic defense system that works like ROS and has a patent to eliminate one of the plants. The seed the main manufacturing vehicle to manufacture high quality technology, is a uniform use of high quality plants, which is a uniform use of high quality plants, which is a uniform use for the crop, and results in a great degree of importance for the culture, and have as a result a great importance for the culture in order to reduce the time of exposure of the seed to the bad weather. Physical conditioning in the use of flags is an alternative to establishing rapid and uniform growth in the field. This technique has the advantages of increasing speed, uniformity of plant emergence and signaling stress response scales. Therefore, research was carried out in order to assess physical conditioning and conditioning modification, changes amidst changes in rice conditions suitable for antioxidant enzyme activity, by lipid oxidation and hydrogen peroxide.